Synergistic anticancer effects of everolimus (RAD001) and Rhein on gastric cancer cells via phosphoinositide-3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway. Issue 3 (1st March 2022) - Gao, Feng; Li, Rui; Wei, Pei-Feng; Ou, Li; Li, Min; Bai, Yang; Luo, Wen-Jia; Fan, Zheng
ABSTRACT: Everolimus (RAD001) is a mTOR inhibitor and is widely used for the treatment of gastric cancer (GC). Evidence suggests that Rhein has anticancer effect on GC. But the synergistic effect and mechanism of RAD001 and Rhein combination on GC is not clear. The current study aims to clarify the combination of RAD001 and Rhein in GC treatment. We found Rhein dose-dependently repressed MGC-803 cell viability (50% inhibition concentration (IC50) value = 94.26 μM). Rhein (80 μM) significantly suppressed GC cell proliferation and invasion. RAD001 dose-dependently repressed MGC-803 cells viability (IC50 value = 45.41 nM). The combination of Rhein and RAD001 repressed MGC-803 cells viability, invasion, and proliferation compared to the administration of Rhein or RAD001 alone. Protein levels of epithelial-mesenchymal transition (EMT)-related molecules E-cadherin, N-cadherin and Vimentin expressions were significantly affected by the combination of Rhein and RAD001. The combination of Rhein and RAD001 significantly facilitated cell apoptosis and up-regulated expressions of cell apoptosis and cycle-related protein p53, cyclin-dependent kinase 4 (CDK4) and cyclin D1 compared to the administration of Rhein or RAD001 alone. Moreover, the combination of Rhein and RAD001 repressed the expressions of phosphorylation-phosphoinositide-3-kinase (p-PI3K), p-protein kinase B (p-AKT) and p-mammalian target of rapamycin (p-mTOR). Finally, the combination of RAD001 and Rhein significantly decreased tumor weight and volume, suppressed the expressions of p-PI3K, p-Akt and p-mTOR, and repressed cell proliferation marker Ki-67 expression, which exerted synergistic cancer prevention in GC in vivo . Overall, the combination of Rhein and RAD001 exert synergistic cancer prevention in GC via PI3K/Akt/mTOR pathway.